Scoliosis Secondary to Lumbar Spine Herniated Nucleus Pulposus in Adolescents: A Case Report - Taif Alqahtani; Faisal Konbaz (Journal of Spine Practice)
Introduction: Herniated nucleus pulposus (HNP) is infrequent among children and adolescents. The first case of surgical intervention for disc herniation was reported in a 12-year-old child. Since then, very few cases or series of cases have been published. The reactive scoliosis is frequently associated with lumbar HNPs, a compensatory effort to relieve nerve compression. Moreover, reactive scoliosis secondary to lumbar HNP is typically associated with children and usually resolves with effective management of lumbar HNP. Although the surgical intervention is frequently employed among adults, only 0.5% of discectomies are carried out in children <16 years old.  The current case report is of a 15-year-old girl, with no history of spinal ailment, who presented with a large disc herniation at L4–L5 region, associated with a reactive secondary scoliosis, which was resolved following a successful surgical intervention.